Analisis Pengaruh Pertumbuhan Ekonomi,Pengangguran, Pendidikan, UMR Dan Pengeluaran Pemerintah Terhadap Tingkat Kemiskinan Di Provinsi Jawa Tengah Tahun 2011-2014 - Putri Arumsari, Fredila; , Drs. Yuni Prihadi Utomo, MM (2017)
The study examined about the influence of economic growth, unemployment, education, the regional minimum wage, and goverment spending towards poverty levels in Central Java province in 2011-2014. Types of data used in this study was the combined data from the secondary data time series and cross section data from 2011-2014. The data used obtained from the official website of the Central Bareau of statistic the Central Java province. Methods of analysis used is regression analysis of the data panel. The result showed the economic growth and unemployment variables do not affect significantly to poverty levels in Central Java province in 2011-2014, while the goverment expenditure variables, the regional minimum wage, and influential education significantly to poverty levels in Central Java province in 2011-2014. The value of the coefficient of determination of 0.990829 which means that free variables are economic growth, unemployment, education, the regional minimum wage and goverment spending affect the 99.08% variable rate of poverty in the Central Java province. Simultaneous test result (test F), indicating that economic growth, unemployment, education the regional minimum wage and simultaneously influential goverment spending significantly to the level of poverty in the Central Java province